Draft genome sequence of mycoplasma arginini strain NGR_2017 (2018)
We present the draft genome of Mycoplasma arginini strain NGR_2017. This strain was recovered in Nigeria from cell culture in 2017. The assembly contains 620,555 bp in 12 contigs. It contains 561 coding sequences, 34 RNAs (29 tRNAs, 4 rRNAs, and 1 transfer-messenger RNA [tmRNA]), and a_26-kb integrative and conjugative element.